Short-term capital flows and monetary management / Mazlan Alias - Alias, Mazlan (1995)
The objective of this study is to examine the factors that influence the short-term capital movements in Malaysia for the past 15 years. This paper also try to examine the relationship between four variables and to evaluate the significance of these variables in influencing the magnitude and direction of short-term capital. From the regression result, this paper suggests several general strategies that can be used in controlling the magnitude of the flows. The general strategies suggested are more to the monetary measure that can be used in the control and regulation process. From the regression analysis, it is found that the most significant factors that influence the magnitude and direction of the inflows of short term capital are the increase in activities in the Kuala Lumpur Stock Exchange (KLSE), followed by the interest rate differentials in favor to Malaysia that stimulate short-term funds to come in. It is found that there is no relationship between the inflows of short term capital to the GDP and the movements of ringgit exchange rate. It is suggested that this is due to the investors' perception and character that never regard the GDP as an important factor. The GDP is more important when the investment is for long-term. The-high return in KLSE can absorb the exchange loss to make the foreign investors ignored the movements in exchange rates as important.